2002
DOI: 10.1002/ppul.10156
|View full text |Cite
|
Sign up to set email alerts
|

Series of laryngomalacia, tracheomalacia, and bronchomalacia disorders and their associations with other conditions in children

Abstract: Laryngomalacia, bronchomalacia, and tracheomalacia are commonly seen in pediatric respiratory medicine, yet their patterns and associations with other conditions are not well-understood. We prospectively video-recorded bronchoscopic data and clinical information from referred patients over a 10-year period and defined aspects of interrelationships and associations. Two hundred and ninety-nine cases of malacia disorders (34%) were observed in 885 bronchoscopic procedures. Cough, wheeze, stridor, and radiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
116
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(130 citation statements)
references
References 27 publications
8
116
0
6
Order By: Relevance
“…14,15 Ian et al had noted that the risk of respiratory illnesses in the malacia group was twice that of the control group. 13 In total, chronic cough was present in 30% of children with airway malacia in the present study. A similar observation was also made by Marchant who showed that a significant number of children with chronic cough have malacia disorders.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…14,15 Ian et al had noted that the risk of respiratory illnesses in the malacia group was twice that of the control group. 13 In total, chronic cough was present in 30% of children with airway malacia in the present study. A similar observation was also made by Marchant who showed that a significant number of children with chronic cough have malacia disorders.…”
Section: Discussionmentioning
confidence: 93%
“…12 Bronchomalacia was observed to be more common on the left side (5 against 1 case) while those with tracheobronchomalacia had bronchomalacia more frequently on the right side (5 against 1 case). Ian Masters et al had also observed that airway malacias were common on the left side 13 while Yalcin and colleagues 10 had noted that malacia disorders were more commonly on the right.…”
Section: Discussionmentioning
confidence: 95%
“…The congenital form of TBM is well described in the pediatric literature [68][69][70], and may be associated with other congenital conditions. The adult forms of TBM are idiopathic or acquired during the course of other illnesses, and are disorders of middle-aged and older persons.…”
Section: Tracheobronchomalaciamentioning
confidence: 97%
“…It is generally a benign condition and usually self-limited, because dynamic airway collapse improves as the airway structures mature. The airway that is maintained during spontaneous breathing could be altered by positive airway pressure changes in patients with airway malacia [3]. When the trachea is compressed or functional narrowing occurs, intermittent respiratory obstruction and arterial desaturation may occur [4][5][6].…”
mentioning
confidence: 99%